The experiences of adult heart, lung, and heart-lung transplantation recipients: A systematic review of qualitative research evidence. - Claire Stubber; Maggie Kirkman (PLoS ONE, 2020)
Aim To review evidence about the experience of being the recipient of a donated heart, lungs, or heart and lungs. Design A systematic review (registered with PROSPERO: CRD42017067218), in accordance with PRISMA guidelines. Data sources Seven databases and Google Scholar were searched in May 2017 and July 2019 for papers reporting English-language research that had used qualitative methods to investigate experiences of adult recipients. Review methods Quality was assessed and results were analysed thematically. Results 24 papers (reporting 20 studies) were eligible and included. Their results were organised into three chronological periods: pre-transplant (encompassing the themes of 'dynamic psychosocial impact', 'resources and support'), transplant ('The Call', 'intensive care unit'), and post-transplant ('dynamic psychosocial impact', 'management', 'rejection'). Sub-themes were also identified. It was evident that contemplating and accepting listing for transplantation entailed or amplified realisation of the precipitating illness's existential threat. The period surrounding transplantation surgery was marked by profound, often surreal, experiences. Thereafter, although life usually improved, it incorporated unforeseen challenges. The transplantation clinic remained important to the recipient. The meaning of the clinic and its staff could be both reassuring (providing care and support) and threatening (representing onerous medical requirements and potential organ rejection). Conclusion This review has implications for the psychosocial care of transplant recipients and indicates the need for further research to gain insight into the experience of receiving a donated heart and/or lung. Impact Medical consequences of heart and lung transplantation are well documented; this is the first systematic review of research using qualitative methods to investigate the experience of heart, lung, and heart-and-lung transplantation. The psychosocial impact of transplantation was found to be dynamic and complex, with notable features evident before, during, and after transplantation. Clinic staff remained significant to recipients. It is clear that recipients need continuing psychosocial as well as medical support.